Multiparametric Renal MRI: An Intrasubject Test–Retest Repeatability Study - Boer, Anneloes; Harteveld, Anita A.; Stemkens, Bjorn; Blankestijn, Peter J.; Bos, Clemens; Franklin, Suzanne L.; Froeling, Martijn; Joles, Jaap A.; Verhaar, Marianne C.; Berg, Nico; Hoogduin, Hans; Leiner, Tim (Journal of magnetic resonance imaging, 2021)
Background Renal multiparametric magnetic resonance imaging (MRI) is a promising tool for diagnosis, prognosis, and treatment monitoring in kidney disease. Purpose To determine intrasubject test–retest repeatability of renal MRI measurements. Study Type Prospective. Population Nineteen healthy subjects aged over 40 years. Field Strength/Sequences T1 and T2 mapping, R2* mapping or blood oxygenation level‐dependent (BOLD) MRI, diffusion tensor imaging (DTI), and intravoxel incoherent motion (IVIM) diffusion‐weighted imaging (DWI), 2D phase contrast, arterial spin labelling (ASL), dynamic contrast enhanced (DCE) MRI, and quantitative Dixon for fat quantification at 3T. Assessment Subjects were scanned twice with ~1 week between visits. Total scan time was ~1 hour. Postprocessing included motion correction, semiautomated segmentation of cortex and medulla, and fitting of the appropriate signal model. Statistical Test To assess the repeatability, a Bland–Altman analysis was performed and coefficients of variation (CoVs), repeatability coefficients, and intraclass correlation coefficients were calculated. Results CoVs for relaxometry (T1, T2, R2*/BOLD) were below 6.1%, with the lowest CoVs for T2 maps and highest for R2*/BOLD. CoVs for all diffusion analyses were below 7.2%, except for perfusion fraction (FP), with CoVs ranging from 18–24%. The CoV for renal sinus fat volume and percentage were both around 9%. Perfusion measurements were most repeatable with ASL (cortical perfusion only) and 2D phase contrast with CoVs of 10% and 13%, respectively. DCE perfusion had a CoV of 16%, while single kidney glomerular filtration rate (GFR) had a CoV of 13%. Repeatability coefficients (RCs) ranged from 7.7–87% (lowest/highest values for medullary mean diffusivity and cortical FP, respectively) and intraclass correlation coefficients (ICCs) ranged from −0.01 to 0.98 (lowest/highest values for cortical FP and renal sinus fat volume, respectively). Data Conclusion CoVs of most MRI measures of renal function and structure (with the exception of FP and perfusion as measured by DCE) were below 13%, which is comparable to standard clinical tests in nephrology. Level of Evidence 2 Technical Efficacy Stage 1